2010
DOI: 10.3113/fai.2010.0141
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intraobserver Reliability in the Radiographic Evaluation of Adult Flatfoot Deformity

Abstract: Adult acquired flatfoot deformity is a complex condition that is difficult to quantify radiographically. The medial cuneiform/fifth metatarsal distance and the calcaneal pitch angle were found to have the highest interobserver reliability. Intraobserver reliability increased with observer experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 8 publications
3
51
1
3
Order By: Relevance
“…The averages of the first and second measurement were calculated and were used in all subsequent analyses. Intraclass correlation coefficients between the initial and second set of measurements were calculated and ranged from 0.61 to 0.99 (Table 1), similar to those obtained in other examinations of foot morphology (Sensiba et al 2010;Younger et al, 2011;Mall et al, 2006). The Kruskal-Wallis test was used to detect differences in measurements between sexes.…”
Section: Methodsmentioning
confidence: 50%
“…The averages of the first and second measurement were calculated and were used in all subsequent analyses. Intraclass correlation coefficients between the initial and second set of measurements were calculated and ranged from 0.61 to 0.99 (Table 1), similar to those obtained in other examinations of foot morphology (Sensiba et al 2010;Younger et al, 2011;Mall et al, 2006). The Kruskal-Wallis test was used to detect differences in measurements between sexes.…”
Section: Methodsmentioning
confidence: 50%
“…While Younger et al (14) reported that the TFMA was an accurate radiographic identifier, Sensiba et al (15) suggested that CPA had a higher interobserver reliability. The relationships of the PAL method with CPA, LTCA, and TFMA were examined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies comparing the radiological measures for diagnosing flatfoot (8,(13)(14)(15), there is no consensus on the radiologic evaluation of the MLA. While Younger et al (14) reported that the TFMA was an accurate radiographic identifier, Sensiba et al (15) suggested that CPA had a higher interobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankle anteroposterior radiography excluded the possibility of valgus at the talotibial joint evidenced by talar tilt in the ankle mortise [8]. In the anteroposterior view of the foot the anterior talocalcaneal angle (TCA1) or Kite's angle, talonavicular angle (TNA), talonavicular coverage angle (TNCA), and anterior talo-first metatarsal angle (TFMA1) were measured.…”
Section: Radiographic Assessmentmentioning
confidence: 99%